Individual and Combined Effects of Cyclodextrins, Poloxamer and PVP on the Solubility and Dissolution Rate of BCS Class II Drugs - Chowdary, K.P.R.; Surya Prakasa Rao, K. (Asian Journal of Chemistry, 2011)
The objective of the study is to evaluate the individual main and combined (or interaction) effects of two cyclodextrins (β-cyclodextrins and hydroxy propyl β-cyclodextrins), surfactant (poloxamer 407) and poly(vinyl pyrrolidone) (PVP) on the solubility and dissolution rate of etoricoxib and nimesulide, two BCS class II drugs in a series of 23 factorial experiments. The solubility of (i) etoricoxib and (ii) nimesulide each in eight selected fluids containing CDs, poloxamer 407 and PVP as per 23 factorial study was determined. The solubility of etoricoxib was markedly enhanced by β-cyclodextrins (2.24 fold), hydroxy propyl β-cyclodextrins (3.14 fold), poloxamer 407 (2.58 fold) and PVP (1.38 fold) individually. β-cyclodextrins in combination with PVP has given highest enhancement (3.44 fold) in the solubility of etoricoxib. Hydroxy propyl β-cyclodextrins in combination with poloxamer 407 and PVP gave respectively 3.74 and 3.39 fold increase in the solubility of etoricoxib. The solubility of nimesulide was also markedly enhanced by β-cyclodextrins (4.12 fold), hydroxy propyl β-cyclodextrins (21.06 fold), poloxamer 407 (5.37 fold) and PVP (24.9 fold) individually. β-Cyclodextrins in combination with poloxamer 407 and PVP gave respectively 5.44 and 26.31 fold increase in the solubility of nimesulide. Hydroxy propyl β-cyclodextrins in combination with poloxamer 407 and PVP gave respectively 5.31 and 26.43 fold increase in the solubility of nimesulide. Poloxamer 407 in combination with PVP has given highest enhancement (28.06 fold) in the solubility of nimesulide. Both the individual and combined effects of cyclodextrins, poloxamer and PVP on the solubility of (i) etoricoxib and (ii) nimesulide were highly significant (P < 0.01). Solid inclusion complexes of drug-cyclodextrins (β-cyclodextrins and hydroxy propyl β-cyclodextrins) were prepared with and without poloxamer 407 and PVP by kneading method as per 23-factorial design in each case. ANOVA indicated that the individual main effects of cyclodextrins (β-cyclodextrins and hydroxy propyl-β-cyclodextrins), poloxamer 407 and PVP and their combined effects in enhancing the dissolution rate (K1) were highly significant (P < 0.01) with both (i) etoricoxib and (ii) nimesulide. β-cyclodextrins alone gave a 1.18 fold increase in the dissolution rate of etoricoxib. β-Cyclodextrins in combination with PVP and poloxamer 407 gave respectively 3.0 and 7.4 fold increase in the dissolution rate of etoricoxib. Hydroxy propyl β-cyclodextrins alone gave a 3.55 fold increase and in combination with PVP and poloxamer 407 it gave respectively 57.6 and 23.6 fold increase in the dissolution rate of etoricoxib. β-cyclodextrins alone gave a 9.63 fold increase in the dissolution rate of nimesulide. Where as in combination with PVP and poloxamer 407 it gave respectively 15.51 and 21.78 fold increase in the dissolution rate of nimesulide. Hydroxy propyl β-cyclodextrins alone gave a 10.88 fold increase and in combination with PVP and poloxamer 407 it gave respectively 37.72 and 51.61 fold increase in the dissolution rate of nimesulide. Thus combination of cyclodextrins with poloxamer 407 and PVP has markedly enhanced both the solubility and dissolution rate of etoricoxib and nimesulide.